One Does (Not) Choose Their Enemies. Why Is America against All? - S. K. Babkina (Сравнительная политика)
Book review: America against All [Amerika protiv vsekh] (2023). Geopolitics, Statehood and Global Role of the USA: History and Modernity [Geopolitika, gosudarstvennost’ i global’naya rol’ SSHA: istoriya i sovremennost’]. Moscow: LLC “Commonwealth of Cultures” [OOO “Sodruzhestvo kul’tur”], 588 p.What is America for Russia, the rest of the world and itself? This question is answered differently by historians, journalists, writers, diplomats, academic researchers, and incumbent politicians. Why has the United States – in recent years especially – pursued an exemplarily offensive foreign policy, as if directed “against everyone”? The authors of the book of the same name, “America Against All. Geopolitics, Statehood and the Global Role of the United States: History and Modernity” offer their answer to this question. The authors of the monograph analyze a significant body of literature on the U.S. geopolitical thought, reflect on the origins of American statehood, and seek to trace the formation of the so-called ‘‘American empire” and the spread of American hegemony from the late 19th century to the present day. In conclusion, the authors outline proposals for democratizing modern America. This book review is an attempt to critically analyze the assessments and recommendations of a large number of authors from the Diplomatic Academy, IMEMO RAS, MGIMO University, RUDN, and branch institutes of the Russian Academy of Sciences.